The development of international cooperation to counter organized crime: the choice of values of the international communit - A. I. Efimova (Vestnik MGIMO-Universiteta, 2010)
Транснациональная организованная преступность в XXI веке представляет глобальную проблему в связи с вызовами международной безопасности и развития. Эта проблема требует комплексного ответа со стороны международного сообщества. Мир без преступности является одним из ценностных ориентиров человеческого развития в условиях глобализации. Конвенция ООН против транснациональной организованной преступности (2000 г.) предложила механизмы по предупреждению и борьбе с транснациональными преступлениями, сформировала принципы универсального понимания криминальных угроз и императивов их преодоления на многосторонней основе. Summary: Transnational organized crime in the 21st century constitutes a global threat to international security and development, thus entailing a multifaceted respond from the international community. The world without crime has become a crucial value of the mankind development agenda within logic of globalization. The UN Convention against Transnational Organized Crime (2000) has provided a framework for international cooperation, formulated principles of universal understanding of criminal threats and importance of combatting them on a multilateral basis.